Distribution of underwriting surplus and investment profit from Tabarru’ fund: Shariah contracts applied and current market practice - Ibrahim, Ahmad Basri; Mohd Ali, Ahmad Fadhil Hamdi; Elias, Mohd Hafizal; Wan Ahmad Lotfi, Wan Ahmad Najib (2015)

(untitled)
Takaful is a contract whereby the participants commit to contribute an amount on regular basis or in one lump sum in a specified fund to mutually guarantee each other and appoint a body to act as the fund manager. In this contract, takaful participants have the opportunity to mitigate the possible financial risk that their families might encounter in case a misfortune happens to them. The contribution then will be placed into respective participant’s account or also known as Participants’ Investment Fund (PIF). The fund manager, i.e. takaful operator will drip from every PIF certain amount on the basis of donation into a collective Participants’ Risk Fund (PRF). Tabarru’ is Arabic word which means donation and due to the nature of PRF, it’s widely known in Islamic Finance as Tabarru’ Fund. Tabarru’ Fund is a separate entity from Takaful operator and participants, but t ownership remains with the participants. Being a fund, some money in it will be invested and would possibly realize investment profit. At the same time, with proper management of the Tabarru’ Fund, it might produce underwriting surplus after payment of claims at the end of financial year. There are several Shariah views and methods on the treatment of the investment profit and underwriting surplus generated from the fund. These views differ from one another depending on the contract adopted, which ultimately would define the permissibility of sharing the surplus between related parties. In Malaysia, the sharing of underwriting surplus is allowed according to the Shariah resolution passed by Central Bank of Malaysia (Bank Negara Malaysia) subject to certain guidelines. All eleven Takaful operators in Malaysia have different practices in distributing the surplus and profit with respect to Shariah contracts applied and operational treatments. This research will study these differences and provide recommendations on the identified issues.